Podocyte VEGF-A Knockdown Induces Diffuse Glomerulosclerosis in Diabetic and in eNOS Knockout Mice - Veron, Delma; Aggarwal, Pardeep K.; Li, Qi; Moeckel, Gilbert; Kashgarian, Michael; Tufro, Alda (Frontiers in Pharmacology, 2022)
Vascular endothelial growth factor-a (VEGF-A) and nitric oxide (NO) are essential for glomerular filtration barrier homeostasis, and are dysregulated in diabetic kidney disease (DKD). While NO availability is consistently low in diabetes, both high and low VEGF-A have been reported in patients with DKD. Here we examined the effect of inducible podocyte VEGF-A knockdown (VEGFKD) in diabetic mice and in endothelial nitric oxide synthase knockout mice (eNOS-/-). Diabetes was induced with streptozotocin using the Animal Models of Diabetic Complications Consortium (AMDCC) protocol. Induction of podocyte VEGFKD led to diffuse glomerulosclerosis, foot process effacement and GBM thickening in both diabetic mice with intact eNOS and in non-diabetic eNOS-/-:VEGFKD mice. VEGFKD diabetic mice developed mild proteinuria and maintained normal glomerular filtration rate (GFR), associated with extremely high NO and thiol urinary excretion. In eNOS -/- :VEGFKD (+dox) mice severe diffuse glomerulosclerosis was associated with microaneurisms, arteriolar hyalinosis, massive proteinuria and renal failure. Collectively, data indicate that combined podocyte VEGF-A and eNOS deficiency result in diffuse glomerulosclerosis in mice; compensatory NO and thiol generation prevents severe proteinuria and GFR loss in VEGFKD diabetic mice with intact eNOS, whereas VEGFKD induction in eNOS-/-:VEGFKD mice causes massive proteinuria and renal failure mimicking DKD in the absence of diabetes. Mechanistically, we identify VEGFKD-induced abnormal S-nitrosylation of specific proteins, including 3- integrin, laminin and S-nitrosoglutathione reductase (GSNOR), as targetable molecular mechanisms involved in the development of advanced diffuse glomerulosclerosis and renal failure.